Complicated trafficking behaviors involved in paradoxical regulation of sortilin in lipid metabolism. Issue 4 (14th October 2019) - Sun, Sha; Yang, Jing; Xie, Wei; Peng, Tianhong; Lv, Yuncheng
Abstract: This review aims to summarize and discuss the most recent advances in our understanding of the underlying mechanisms of the paradoxical effects of sortilin on lipid metabolism. The vacuolar protein sorting 10 protein (Vps10p) domain in the sortilin protein is responsible for substrate binding. Its cytoplasmic tail interacts with adaptor molecules, and modifications can determine whether sortilin trafficking occurs via the anterograde or retrograde pathway. The complicated trafficking behaviors likely contribute to the paradoxical roles of sortilin in lipid metabolism. The anterograde pathway of sortilin trafficking in hepatocytes, enterocytes, and peripheral cells likely causes an increase in plasma lipid levels, while the retrograde pathway leads to the opposite effect. Hepatocyte sortilin functions via the anterograde or retrograde pathway in a complicated and paradoxical manner to regulate apoB‐containing lipoprotein metabolism. Clarifying the regulatory mechanisms underlying the trafficking behaviors of sortilin is necessary and may lead to artificial sortilin intervention as a potential therapeutic strategy for lipid disorder diseases. Conclusively, the paradoxical regulation of sortilin in lipid metabolism is likely due to its complicated trafficking behaviors. Abstract : Regulatory mechanisms of sortilin in bidirectional trafficking paradoxical roles of sortilin in lipid metabolism. Bidirectional trafficking behaviors likely contribute to the paradoxical regulatory roles of sortilin in lipid metabolism.